EFFECT OF HEALTH EDUCATION OF SLEEP HYGIENE ON SLEEP PROBLEMS IN PRESCHOOLERS - Eka Wahyuningrum; Sri Hartini; Ibrahim Rahmat (Belitung Raya Foundation, Indonesia, 2018)
Background: Children need adequate sleep for good health status. Without a balanced sleep, it will encourage the emergence of serious health or developmental problems. Previous studies showed more than 40% of preschoolers experienced sleep problems. Objective: To examine the effect of HESH (Health Education of Sleep Hygiene) on sleep problems in preschoolers. Methods: Pretest posttest design non-equivalent control group was used in this study. Sixty participants recruited by consecutive sampling. Parents in the experimental group received health education using power point and booklet HESH for 100 minutes, parents in the control group received health education using power point for 100 minutes without booklet HESH. Telephone follow up was done for evaluation program. Sleep problem was measured with Children’s Sleep Habits Questionnaire (CSHQ) completed by children’s parents. Data analysis used unpaired t-test with 95% confidence interval. Results: The result showed that there was effect of HESH toward sleep problems in preschooler (experimental group: -3.367±5.269; control group: 0.033±5.061, p= 0.015). Conclusion: HESH in parents could decrease sleep problems in preschoolers in Indonesia. It is expected that HESH can be used as an alternative nursing intervention involved parents to decreases sleep problem in preschooler.